2014
DOI: 10.1002/cncr.28979
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutation in patients undergoing hepatic resection for colorectal liver metastasis: A biomarker of cancer biology or a byproduct of patient selection?

Abstract: Patients with colorectal cancer have experienced remarkable progress in a range of surgical and oncologic management strategies over the past few years, with a corresponding improvement in survival. The KRAS mutation may be a biomarker of cancer biology and prognosis, but also reflects patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The prognostic value of the KRAS genotype among patients with CRLM has been controversial [18]. While several investigators have reported that KRAS status has prognostic value, other investigators have failed to note an association of mut KRAS with worse survival [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prognostic value of the KRAS genotype among patients with CRLM has been controversial [18]. While several investigators have reported that KRAS status has prognostic value, other investigators have failed to note an association of mut KRAS with worse survival [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…end, Soreide et al have criticized previous studies for possible bias due to the highly selective manner in which patients were included in these study cohorts [18]. In fact, Soreide et al questioned whether the apparent prognostic impact of KRAS status was a by-product of patient selection or would persist among a more "unselected" cohort [18].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
See 2 more Smart Citations
“…Vogelaar et al also confirmed a trend toward poorer prognosis in patients with mutant KRAS or BRAF (12). The negative impact of these mutations has been noted by others in both early-and late-stage colorectal cancer (CRC) (11,(14)(15)(16). Strikingly, the high mutation rate of BRAF in the study by Vogelaar et al (19%) should be noted, as this rate is usually reported as a single-digit percentage, typically at 5-8% (17).…”
Section: Resultsmentioning
confidence: 76%